Better way to image and manage Neuroendocrine Tumours: Role of 68Gallium DOTA-Peptide PET-CT scan - Dey, Shankar Kumar (Bangladesh Journal of Nuclear Medicine, 2018)
Neuroendocrine tumours (NETs) are special entity of neoplasms arising from nervous and endocrine systems and involving variety of organs. Over expression of somatostatin receptors is an unique characteristic of these tumours. This allows molecular imaging to play a significant role in evaluation of NETs using somatostatin analogues. 111 In Pentetreotide scintigraphy has been playing a significant role as molecular imaging of choice to locate the primary tumor, evaluate extent of disease and plan for surgical management. Recently 68 Ga labelled peptides have emerged as promising PET tracers for scintigraphy of these tumours. Several recent studies have demonstrated the superiority of 68Ga DOTA- Peptide PET-CT scan with a number of advantages over conventional somatostatin receptor scintigraphy. Bangladesh J. Nuclear Med. 20(2): 136-142, July 2017